SISTEM INFORMASI PENGANGKUTAN KOMODITAS (CANGKANG DAN KERNEL) PADA PT MITRA ABADI DAMAI JAMBI BERBASIS WEB: System;Processing;Transport;Codeigneter Framework;M-V-C. - Mulyati, Sri; Claudia Tambunan, Ester (LP2M Universitas Nurdin Hamzah, 2022)
Mitra Abadi Damai Jambi is one of company that moves in transport service and in processing still using books and counting tools .So that problems occur that is a mistake in recording and the reckoning total money of transport, hard to perform for finding transport data, and in recording data report took quite relatively long time. Hence, this study aims to give solution to the problem by offering processing transport data system use PHP programming language and database MySQL.The new system produce outputs featuring user data, driver data, car data,route data, transportation data and data of charge in structured and display reports necessary to ease.